How Medicare Part D Benefit Phases Affect Adherence with Evidence‐Based Medications Following Acute Myocardial Infarction. (6th June 2013) - Stuart, Bruce; Davidoff, Amy; Erten, Mujde; Gottlieb, Stephen S.; Dai, Mingliang; Shaffer, Thomas; Zuckerman, Ilene H.; Simoni‐Wastila, Linda; Bryant‐Comstock, Lynda; Shenolikar, Rahul
Abstract : Objective: Assess impact of Medicare Part D benefit phases on adherence with evidence‐based medications after hospitalization for an acute myocardial infarction. Data Source: Random 5 percent sample of Medicare beneficiaries. Study Design: Difference‐in‐difference analysis of drug adherence by AMI patients stratified by low‐income subsidy (LIS) status and benefit phase. Data Collection/Extraction Methods: Subjects were identified with an AMI diagnosis in Medicare Part A files between April 2006 and December 2007 and followed until December 2008 or death ( N = 8, 900). Adherence was measured as percent of days covered (PDC) per month with four drug classes used in AMI treatment: angiotensin‐converting enzyme (ACE) inhibitors/angiotensin II receptor blockers (ARBs), beta‐blockers, statins, and clopidogrel. Monthly exposure to Part D benefit phases was calculated from flags on each Part D claim. Principal Findings: For non‐LIS enrollees, transitioning from the initial coverage phase into the Part D coverage gap was associated with statistically significant reductions in mean PDC for all four drug classes: statins (−7.8 percent), clopidogrel (−7.0 percent), beta‐blockers (−5.9 percent), and ACE inhibitor/ARBs (−5.1 percent). There were no significant changes in adherence associated with transitioning from the gap to the catastrophic coverage phase. Conclusions: As the Part D doughnut hole is gradually filled in by 2020, Medicare Part D enrollees with critical diseases such as AMI who rely heavily on brand name drugs are likely to exhibit modest increases in adherence. Those reliant on generic drugs are less likely to be affected.